2022
DOI: 10.1002/cpt.2556
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Hepatobiliary Clearances and Hepatic Concentrations of Transported Drugs in Humans Using Rosuvastatin as a Model Drug

Abstract: Study HighlightsWHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC?  Accurate prediction of tissue concentrations of a drug is important to understand its pharmacokinetic/pharmacodynamic (PK/PD) relationship. However, making such predictions is challenging, especially when the drug is a substrate of the tissue uptake and/or efflux transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The next frontier in this area of research is to predict and validate fetal tissue drug exposure. We have already shown that the ER‐REF approach is successful in predicting human adult brain and liver drug concentrations where the drugs are actively transported across the tissue : blood barrier 126,127 . Thus, there is every reason to believe that this approach will be successful in predicting fetal tissue drug exposure provided the relevant data on the ontogeny of transporters and enzymes in these tissues are available.…”
mentioning
confidence: 99%
“…The next frontier in this area of research is to predict and validate fetal tissue drug exposure. We have already shown that the ER‐REF approach is successful in predicting human adult brain and liver drug concentrations where the drugs are actively transported across the tissue : blood barrier 126,127 . Thus, there is every reason to believe that this approach will be successful in predicting fetal tissue drug exposure provided the relevant data on the ontogeny of transporters and enzymes in these tissues are available.…”
mentioning
confidence: 99%
“…In conclusion, using the REF approach, we have now successfully predicted CL s,uptake , CL s,efflux , CL bile , and human hepatic concentrations of the drugs, GLB, PTV, and RSV 8 that are transported by multiple transporters (OATPs, NTCP, MRP2, MRP3, BCRP, and P‐gp). In addition, we have verified the ability of the TECs/REF approach to predict the brain and fetal unbound tissue‐to‐plasma concentration ratio of several transported substrates 10–12 .…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the REF‐predicted mean GLB AUC and C max were not significantly different from those observed ( P > 0.05). Whereas the prediction of hepatic 18 F‐PTV AUC and C max met the success criteria, like RSV 8 the hepatic concentration‐time profile was modestly underpredicted due to underprediction of its CL s,uptake . We note that modest underprediction of this magnitude has also been widely reported for IVIVE of metabolic CL of drugs 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations